THE ROLE OF THE SYSTEM OF TUTORING IN HIGHER EDUCATION AND THE IMPORTANCE OF STUDENTS IN THE PROCESS OF OBTAINING EDUCATION - Nurmatova Madina Odiljon (Journals Park Publishing, 2024)
The current education system is constantly updated and seeks to provide quality education for students. Of particular importance in this process is the system of tutoring, that is, mentoring. This article will consider in detail and problems of the role, benefits, impact on students in modern education.
Keywords: The system of tutoring, higher education, students, educational process, mentoring, academic, achievements, personal development, Professional training, communication between teachers and students